Pengembangan Media Interaktif Articulate Storyline 3 Berbasis Problem Based Learning di Kelas V Sekolah Dasar - Firdha Okta Viola; Atri Waldi (Universitas Negeri Padang, 2023)
The background of this research is the lack of availability of varied and interesting learning media so that it has an impact on students' interest in being active in the learning process. The aim of the research is to develop and create a valid and practical Articulate Storyline 3 interactive media based on Problem Based Learning in fifth grade elementary school. The type of research used is development research (R&D) with the ADDIE model. The results showed that the value of the media validity test from the material aspect was 92.7%, the language aspect was 93.7%, and the media aspect was 91.4%, the criteria were very valid. The practicality test showed that the practicality of the media in terms of teacher and student responses was 95.8%. and 93.1% criteria are very practical. Based on these results, it was concluded that the developed Articulate Storyline 3 interactive media based on Problem Based Learning was very feasible and practical for use in elementary schools.